Potential of Carbon Fiber as An Insulation Layer In Anti-Sensor Thermal Pdl: A Review - Nasution, Rahmatsyah; Murniati, Riri; Nasution, Salsabila Fauziah Dhuha (Journal of Energy, Material, and Instrumentation Technology, 2024)
The advancement of technology, along with the development of the times, makes mastery of technology an absolute thing for the progress of national defense; one of its applications in defense materials is the manufacture of PDL anti-thermal sensor suits. In the PDL anti-thermal sensor suit, carbon fiber is used as insulation. Carbon fiber is a strong, lightweight, and thermal insulator material. This research method uses a qualitative descriptive research method with sources from Google Scholar. In this study, Publish & Perish 8 software was used to help obtain 200 journals on the topics of carbon fiber characteristics, composites, sensors, thermal, carbon fiber resistance generators, carbon fiber thermal conductivity testing, determination of layers of PDL anti-thermal sensor clothes, and the use of carbon fiber as an insulation layer on PDL anti-thermal sensor clothes which were then reviewed as many as 20 journals to be reviewed and summarized for reviewed and summarized to see the potential of carbon fiber as an insulation layer of composite materials in PDL Anti-Thermal Sensor clothing. The conclusion obtained in this study is that carbon fiber has a carbon content of 92% with a solid tensile strength of 452.94 MPa and a low thermal conductivity of 1,13 W/mk and has the potential to be applied as an insulation layer on PDL clothes anti-thermal sensors.